The Toraja Community’s Coping Mechanisms in Dealing with Bereavement due to Death - Harianto Gusti Tau Toding; Reni Lolotandung (Research Horizon, 2026)
Death and loss are universal experiences that may generate significant psychological pressure, particularly within cultural contexts that involve complex funeral rituals. In the Toraja community, the rambu solo’ ceremony represents not only a cultural tradition but also a social and psychological space that shapes individuals’ experiences of grief and adaptation. This study aimed to understand the dynamics of coping mechanisms among Toraja individuals experiencing loss within the context of the rambu solo’ ceremony. This study employed a qualitative approach using a case study method. Data were collected through semi-structured, in-depth interviews. Data were analyzed inductively through open coding, coding, and axial coding. The findings revealed that coping mechanisms in the context of rambu solo’ are complex and multidimensional. Individuals experienced emotional, sociocultural, economic, and ritual-related stressors. Coping strategies involved emotion-focused coping, problem-focused coping, and shifting focus from grief to ritual activities. Social support, cultural values, and the meaning attributed to the ritual influenced the coping process. The coping mechanisms resulted in both positive psychological adaptation and potential distress. These findings highlight the importance of culturally grounded perspectives in understanding coping and psychological adaptation to loss.